Thermomechanical Fatigue of Unidirectional Carbon Fiber/Epoxy Composite in Space - Ali Anvari (Journal of Engineering)
Thermomechanical fatigue is one of the challenges for spacecrafts during space missions. As a result of the extreme temperature variation in space, thermal cycles are created, and due to the imposed mechanical loads to spacecrafts such as engine loads while they turn on and off, mechanical cycles are created. The worst structural fatigue for spacecrafts occurs when both thermal and mechanical cycles happen, simultaneously. The reason is that both thermal and mechanical cycles could cause stress concentration in the spacecraft structure. Therefore, the probability of crack initiation or propagation in the spacecraft structure increases. In this study, for the first time, novel thermomechanical fatigue relations are introduced to evaluate the safety of unidirectional carbon fiber/epoxy composite in the space environment. This composite material has been used in the spacecraft structure due to its lightweight and high strength. Furthermore, with applying thermal fatigue relations, thermally-safe planets, moons, and asteroids in the solar system for unidirectional carbon fiber/epoxy composite are identified.